Analisis Potensi Swabakar (Self-Combustion) Berdasarkan Data Proksimat pada Batubara PT. Geoservices Samarinda - Wahidah, Wahidah; Fajarwati, Delia Aurora; Lepong, Piter; Alamsyah, Andi (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2022)
The self-combustion phenomenon that has the potential to cause fires in the coal mining industry in East Kalimantan is the subject of this study. The purpose of this study is to determine the quality and characteristics of coal that has the potential to trigger self-heating. In this research, 5 (five) samples of coal quality are analyzed from PT. Geoservice Samarinda using the proximate analysis method and analysis of calorific value and total sulfur. Next, determine ranking of coal and analyze the characteristics of coal samples that are prone to potential self-combustion. The results show that the five coal samples included in Sub-Bituminous rank with medium volatile matter considered to have sufficient potential to experience self-combustion. The most susceptible coal sample is sample code D1 because it also has lower inherent moisture and ash content and higher total sulfur content than other coal samples. However, further tests still need to be carried out to determine the percentage of total sulfur (pyrite) as a trigger for self-combustion. Environmental factor analysis is also required for validation.